2014
DOI: 10.1002/ana.24252
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular responses to direct stimulation of the human insular cortex

Abstract: These results demonstrate vestibular sensory processing in the insula that is centered on its posterior part. The present data add to the understanding of the multiple sensory functions of the insular cortex and of the cortical processing of vestibular signals. The data also indicate that lesion or dysfunction in the posterior insula should be considered during the evaluation of vestibular epileptic seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 67 publications
1
50
0
1
Order By: Relevance
“…Interestingly, the pattern of functional connectivity from the TPJ to the insula and the supplementary motor area varied during visuo-tactile stimulation, and reflected experimentallyinduced changes in self-location and first-person perspective. The involvement of the insula in BSC and self-location is in line with the prominent involvement of the insula neurons in the processing of bodily multisensory signals (Craig, 2002(Craig, , 2009Critchley, 2004;Critchley et al, 2004), including vestibular signals (Indovina et al, 2005;Mazzola et al, 2014). The insula is also the primary region processing interoceptive signals (Craig, 2002;Critchley et al, 2004) and has recently been shown to mediate changes in self-identification and self-location based on cardio-visual stimulation in the full-body illusion (Aspell et al, 2013;Ronchi et al, 2015), illusory own-body perceptions due to interoceptive-exteroceptive disintegration in neurological patients and hand ownership (Tsakiris et al, 2007).…”
Section: Self-face Perception and Face Ownershipmentioning
confidence: 55%
“…Interestingly, the pattern of functional connectivity from the TPJ to the insula and the supplementary motor area varied during visuo-tactile stimulation, and reflected experimentallyinduced changes in self-location and first-person perspective. The involvement of the insula in BSC and self-location is in line with the prominent involvement of the insula neurons in the processing of bodily multisensory signals (Craig, 2002(Craig, , 2009Critchley, 2004;Critchley et al, 2004), including vestibular signals (Indovina et al, 2005;Mazzola et al, 2014). The insula is also the primary region processing interoceptive signals (Craig, 2002;Critchley et al, 2004) and has recently been shown to mediate changes in self-identification and self-location based on cardio-visual stimulation in the full-body illusion (Aspell et al, 2013;Ronchi et al, 2015), illusory own-body perceptions due to interoceptive-exteroceptive disintegration in neurological patients and hand ownership (Tsakiris et al, 2007).…”
Section: Self-face Perception and Face Ownershipmentioning
confidence: 55%
“…The stereotactic implantation followed the procedure described in our previous studies (Mazzola et al, ; Mazzola et al, ; Mazzola, Isnard, & Mauguière, ). Electrodes were implanted perpendicular to the midsagittal plane and were left in place chronically up to 15 days.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, temporopolar cortex, although relatively poorly understood as a region, is hypothesized to act as a “paralimbic” area working closely with more canonical limbic areas . Temporopolar cortex shows dense anatomical interconnections to OFC, the insula, the amygdala, and other medial temporal lobe structures . A proposed role of this region is in binding visceral‐affective assessments with highly processed perceptual information—that is, integrating affect with perception, presumably in the service of higher order decision making .…”
Section: Affect In the Self‐generated Thought Of Healthy Populationsmentioning
confidence: 99%